Structural, Functional, and Spectroscopic Characterization of the Substrate Scope of the Novel Nitrating Cytochrome P450 TxtE. Issue 15 (2nd September 2014) - Dodani, Sheel C.; Cahn, Jackson K. B.; Heinisch, Tillmann; Brinkmann‐Chen, Sabine; McIntosh, John A.; Arnold, Frances H.
Abstract A novel cytochrome P450 enzyme, TxtE, was recently shown to catalyze the direct aromatic nitration of L‐tryptophan. This unique chemistry inspired us to ask whether TxtE could serve as a platform for engineering new nitration biocatalysts to replace current harsh synthetic methods. As a first step toward this goal, and to better understand the wild‐type enzyme, we obtained high‐resolution structures of TxtE in its substrate‐free and substrate‐bound forms. We also screened a library of substrate analogues for spectroscopic indicators of binding and for production of nitrated products. From these results, we found that the wild‐type enzyme accepts moderate decoration of the indole ring, but the amino acid moiety is crucial for binding and correct positioning of the substrate and therefore less amenable to modification. A nitrogen atom is essential for catalysis, and a carbonyl must be present to recruit the αB′1 helix of the protein to seal the binding pocket.